Evaluation of Medical Record Digitalization in Outpatient Registration: A Case Study of Diponegoro National Hospital, Indonesia - Saputra, Ilham Imam; Abiyassa, Maulana Tomy; Kusuma, Edi Jaya; Wulan, Widya Ratna (Health Science UDINUS, 2025)
Digitization refers to the process of converting paper-based medical records into electronic format. At Diponegoro National Hospital (RSND), implementation still faces challenges, as some documents are still in manual format. This study employed descriptive qualitative research. This research was conducted through interviews and observations of outpatient registration staff and digitalization staff who digitized electronic outpatient documents. Observations regarding the age characteristics of staff within the productive age group revealed that four respondents (3 men and 1 woman) had worked for 1 year and 5 years, respectively, and had never received training related to the digitization of electronic medical records. The staff learned about this by being taught how to use it by a third party until they understood how to use the system. The system used is the RSND Electronic Medical Record, but some users did not yet understand the application's contents. In-depth statistical analysis of the relationship between outpatient staff knowledge and the implementation of electronic document digitization was not conducted in this study. Strengthening staff competency through structured training and the development of standard operating procedures is crucial to optimize EMR digitization at RSND.